ANALYSIS OF STUDENT LEARNING MOTIVATION USING THE SAVI LEARNING MODEL IN CLASS IV OF SD IT BINA INSAN BATANG QUIZ FOR THE 2023 ACADEMIC YEAR - Agnes, Budi; Ramadhan, Nuri; Safitri, Layil (Transpublika Publisher, 2023)
This study aims to determine the level of student motivation by using the SAVI learning model in the Thematic subjects Theme VI Sub-theme of the life cycle of living things class IV SDIT Bina Insan Batang Kuis. This type of research is descriptive research. The population in this study was grade IV students of SDIT Binan Insan Batang Kuis which amounted to 110 students. The sample in this study was all grade IV students of SDIT Binan Insan Batang Kuis totaling 110 students. Data collection using questionnaires, observations, interviews and documentation. Data analysis techniques use descriptive analysis techniques. From the results of the study, the percentage of motivation with internal encouragement was 78.29% with the high category, and the percentage of motivation with external encouragement was 73.49% with the medium category, while the overall learning motivation of grade IV students of SDIT Binan Insan Batang Kuis for the 2023/2024 Academic Year was a medium category of 75.89%.